A comparative study of the effect of different topical agents on burn wound infections - Katara Gunjan; Chamania Shobha; Chitnis Sheetal; Hemvani Nanda; Chitnis Vikrant; Dhananjay Sadashiv Chitnis (Indian Journal of Plastic Surgery)
Background: Topical agents are used to treat burn wound infections. Aims and Objective: The present work was aimed to find out the in vitro efficacy of different topical agents against burn wound pathogens. Settings and Design: Randomly selected gram-positive (29) and gram-negative bacterial (119) isolates from burn wound cases admitted in burn unit of Choithram Hospital and Research Centre, Indore, were included in the in vitro activity testing for silver nitrate, silver sulphadiazine (SSD), chlorhexidine, cetrimide, nitrofuran, soframycin, betadine, benzalkonium chloride and honey by growth inhibition on agar medium. Materials and Methods: Multidrug-resistant isolates of gram-positive and gram-negative bacteria were checked for different topical agents. 1% topical agent was mixed with Mueller-Hinton agar. Two microlitres of bacterial suspension adjusted to 0.5 McFarland turbidity standard was spread over the topical agent containing plates. The plates without the topical agent were used as control plates. The plates were incubated for 48 h at 37΀C. Results: SSD (148/148), silver nitrate (148/148) and chlorhexidine (148/148) showed excellent activity against all the pathogens. Neosporin had poor activity against Pseudomonas aeruginosa, (4/44) Proteus spp. (2/4) and group D streptococci (1/4). Betadine did not show activity against the bacterial isolates in the presence of organic matter. Honey did not exert any antimicrobial activity under the study conditions. Conclusion: SSD, silver nitrate and chlorhexidine have excellent activity against all the bacterial pathogens and could be used empirically, while identification of the infective agent is required for selecting the alternative topical agents such as nitrofuran, soframycin, and benzalkonium chloride.